2
$\begingroup$

I'm new to this forum and I don't know how to write mathematical symbols. I have the following functional equation:

  • $f$ defined on $[0, +\infty)$ with values in $[0, +\infty)$
  • $f$ is bijective and the following relation holds (*):

$$f^{-1}(f(x)f(y))=\frac{f(x+y)-f(x)-f(y)}2$$ Find all functions with this property. I found that $f(0)=0$ with standard manipulations. $f$ is also continuous (comments). Thank you!

$\endgroup$
  • $\begingroup$ I edited you question to typeset the math with Latex. You may find this information useful: MathJax tutorial $\endgroup$ – rubik Feb 2 '15 at 16:29
  • $\begingroup$ Thank you very much! It seems to be very useful and easy to learn. $\endgroup$ – user212396 Feb 2 '15 at 16:30
  • $\begingroup$ Yes! It is definitely not difficult to learn and has many benefits, first of all in readability. $\endgroup$ – rubik Feb 2 '15 at 16:32
  • $\begingroup$ The above shows that $f(x+y) \ge f(x)+f(y)$ so $f$ is monotonically increasing. Since it is bijective, it must be continuous. $\endgroup$ – copper.hat Feb 2 '15 at 17:43
0
+50
$\begingroup$

It seems the following.

I shall continue from already obtained results. Since the function $f$ is bijective, there exists a point $x_0$ such that $f(x_0)=1$. Putting in the relation (*) $x=x_0$ and $y=nx_0$ we obtain

$$f^{-1}(f(x_0)f(nx_0))=\frac{f((n+1)x_0)-f(x_0)-f(nx_0)}2$$ $$nx_0=\frac{f((n+1)x_0)-1-f(nx_0)}2$$ $$f((n+1)x_0)= f(nx_0)+2nx_0+1$$

From this recurrence, using initial condition $f(x_0)=1$ we obtain

$$f(nx_0)=n+n(n-1)x_0.$$

Putting in the relation (*) $x=2x_0$ and $y=2x_0$ we obtain

$$f^{-1}(f(2x_0)^2)=\frac{f(4x_0)-2f(2x_0)}2$$

$$f^{-1}((2+2x_0)^2)=\frac{4+12x_0-2(2+2x_0)}2$$ $$f^{-1}((2+2x_0)^2)=4x_0$$ $$(2+2x_0)^2=f(4x_0)=4+12x_0$$ $$(1+x_0)^2=1+3x_0$$ $$x_0^2=x_0$$ $$x_0=1$$

So

$$f(n)=n^2.$$

Putting in the relation (*) $x=1$ and $y=y$ we obtain

$$f^{-1}(f(y))=\frac{f(y+1)-f(1)-f(y)}2$$ $$2y=f(y+1)-1-f(y)$$ $$f(y+1)=f(y)+2y+1$$

Iterating this recurrence, we obtain (**)

$$f(y+n)=f(y)+2ny+n^2.$$

Putting in the relation (*) $x=n$ and $y=y$ we obtain

$$f^{-1}(f(n)f(y))=\frac{f(n+y)-f(n)-f(y)}2$$ $$f^{-1}(n^2f(y))=\frac{f(n+y)-n^2-f(y)}2$$

Using (**), we obtain $$f^{-1}(n^2f(y))=ny$$ $$n^2f(y)=f(ny).$$

Therefore for each positive rational number $\frac pq$ we have

$$f\left(\frac pq\right)=\frac 1{q^2}f(p)= \frac {p^2}{q^2}.$$

Since the function $f$ is continuous, for each $x\ge 0$ we have

$$f(x)=x^2.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.